Xerophthalmia In urban Slum Children Of Delhi - Kumar Avdhesh; Mehra Malti; Badhan S.K; Singh Saudan (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the prevalence of xerophthalmia in urban slum children of Delhi? Objectives: 1. To determine the prevalence of xerophthalmia 2. To describe the prevalence by age, sex and parents literacy status. Study design: Cross- sectional study. Setting: Gokulpuri resettlement colony, Delhi. Participants: Under 15 children. Study Variables: Age, sex and parentsâ€ literacy status. Outcome variable: Bitotâ€s spot. Statistical analysis: Chi square test. Results: Overall prevalence of xerophthalmia was 1.2%. Higher prevalence was observed among children aged 10 years and above (1.7%) in comparison to under 5 children (0.6%). Conclusion: School going children also need to be subjected to oral vitamin A supplementation.